PENGGUNAAN ENERGI TERBARUKAN, SKOR ESG, BIAYA MODAL DAN BIAYA OPERASIONAL PADA KINERJA KEUANGAN - Vlaviorine, Emelie; Widianingsih, Luky Patricia (Jurnal Akuntansi Kontemporer, 2023)
Research Purposes. The purpose of this study is to see the effect of financial performance through ROA which is proxied into 5 variables, namely the use of renewable energy, ESG scores, capital costs, and operational costs.Research Methods. The population in this study is the Asian mining industry registered at Refinitiv using a purposive sampling method using 165 samples during 2019- 2020. Data collection uses secondary data that comes from the Refinitiv web. Data analysis used multiple linear regression using SPSS version 26.Research Results and Findings. The results of the study proved that the ESG score and cost of capital variables had a positive effect on financial performance. Meanwhile, the variable use of renewable energy and operational costs has a negative effect on finan- cial performance.